Glutamine supplementation influences the secretory apparatus in the right atrial cardiomyocytes of resistance trained aged rats - Romeu Rodrigues de Souza; Cristiano Ferreira Pacheco; Erico Chagas Caperuto; Laura B.M. Maifrino; Eliane F. Gama
Abstract We investigated the effects of glutamine supplementation on the secretory apparatus of natriuretic peptides in atrial cardiomyocytes of aged rats undergoing resistance training. Two groups of resistance-trained rats were studied: resistance trained, and resistance trained and supplemented with glutamine group. Both groups of rats were trained to climb a 1.1 m vertical ladder with weights tied to their tail. The cardiomyocytes from resistance trained and supplemented rats showed increased density and sectional area of natriuretic peptides granules, higher relative volumes of the mitochondria, endoplasmic reticulum, Golgi complex and nuclear euchromatin, and nuclear pore density compared with resistance trained rats. In conclusion, glutamine supplementation caused hypertrophy of the secretory apparatus in the cardiomyocytes of aged rats undergoing resistance training.